Tilapia-Macrobrachium polyculture - New, Michael B.; Valenti, Wagner C. [UNESP] (Wiley, 2017)
This chapter reviews the scientific research literature on the rearing of tilapia with freshwater prawns (Macrobrachium spp.) in polyculture (and co-culture) up to the beginning of the year 2015. The chapter starts with an introduction to the current global scale of tilapia and freshwater prawn farming. This is followed by a section on prawn-tilapia interactions. The chapter continues with a detailed review of four decades of research into prawn-tilapia polyculture. Following a section on commercial prawn-tilapia polyculture practices, the chapter provides a summary naming the major research centers involved in this topic. Finally, the authors conclude that tilapia and prawns are compatible species for farming through either polyculture or co-culture. Both systems are technically feasible today and can improve the use of natural resources (such as space, water, and nutrients), reduce the use of commercial diets, and increase profits. However, a significant research effort is needed to provide science-based knowledge in order to improve the efficiency of these aquaculture systems and to take full advantage of their potential to achieve a real multitrophic and multispatial equilibrated system (IMTA).
Keywords: Co-culture; Freshwater prawns; IMTA; Macrobrachium; Polyculture; Tilapia